KI-Einsatz durch Lernende im Erkenntnisgewinnungsprozess - ein Review - Fox, Marvin Lee; Peeters, Hendrik; Fechner, Sabine (GDCP Jahrestagung)
Keywords: Artificial intelligence; education; chemistry

Phosphonic acid adsorption on α-Bi2O3 surfaces - Bocchini, Adriana; Kollmann, S.; Gerstmann, Uwe; Schmidt, Wolf Gero; Grundmeier, Guido (Surface Science)

Finite-size and relativistic effects onto hyperfine interaction of muonic hydrogen - Franzke, Katharina L.; Schmidt, Wolf Gero; Gerstmann, Uwe (Journal of Physics: Conference Series)
Abstract Muonic hydrogen is an exotic atom where a muon instead of an electron is bound to a proton. The comparably high mass of the muon (≈ 207 · m e ) has two important effects, (i) the reduced mass of the system becomes more important, and (ii) the muon is localized much closer to the nucleus. Thus, muonic hydrogen is not only excellently suitable for evaluating highly precise quantum electrodynamic (QED) calculations, but may also be used for assessing new approaches including finite nuclear size (FNS) effects to evaluate the proton structure and improve calculation schemes for the hyperfine splittings of many-particle systems, as e.g. to be implemented in density functional theory (DFT) software packages. Here, starting from Dirac’s equation we calculate the relativistic hyperfine splitting of the ground state and several excited states of muonic hydrogen analytically for different charge and magnetization models. The FNS related hyperfine shifts are compared with the differences between QED calculations and experimental measurements. This comparison also allows to unravel the role of the reduced mass, which is on one hand crucial in case of muonic atoms, but on the other hand is by no means well defined in relativistic quantum mechanics.

Dynamic and Reversible Plasmonic Nanogaps From Isolated Dimer Nanoparticles via Self-Assembly - Devaraj, Vasanthan; Ruiz Alvarado, Isaac Azahel; Lee, Jongmin; Oh, Jin-Woo; Gerstmann, Uwe; Schmidt, Wolf Gero; Zentgraf, Thomas (2025 Conference on Lasers and Electro-Optics Europe & European Quantum Electronics Conference (CLEO/Europe-EQEC))

Efficient n‐Doping of Organic Semiconductors via a Broadly Applicable Nucleophilic‐Attack Mechanism - Wei, Huan; Wu, Tong; Dong, Chuanding; Chen, Chen; Gong, Zhenqi; Xia, Jiangnan; Peng, Chengyuan; Ding, Jiaqi; Zhang, Yu; Shi, Wenpei; Schumacher, Stefan; Zhang, Xue; et al. (Advanced Science)
Abstract The development of efficient and broadly applicable n‐doping strategies for organic semiconductors (OSCs) is crucial for advancing the performance of various organic electronic devices. Here, a novel nucleophilic‐attack n‐doping mechanism is unveiled that achieves exceptionally high conductivity in doped OSC films and demonstrates broad applicability across OSCs. The remarkable efficacy of n‐Butyl lithium (n‐BuLi) is highlighted in n‐doping C 60 and PC 61 BM, achieving a conductivity of 1.27 S cm −1 and 2.57 S cm −1 , respectively, which are among the highest reported values for these materials. The investigation reveals that the n‐BuLi anion interacts with electron‐deficient units in OSCs, generating a carbanion that facilitates efficient electron transfer for n‐doping. This mechanism is further validated across diverse fullerenes, polymeric, and small molecule OSCs, and is extendable to other high‐performance dopants such as tert‐Butyllithium (tert‐BuLi) and sodium ethoxide (NaOEt). Device studies show that n‐BuLi‐doped C 60 enables substantially improved diode rectification, attributed to greater junction built‐in potential. These findings establish a unified chemical‐bonding‐based n‐doping paradigm, complementing existing electrophilic‐attack p‐doping concepts, and pave the way for achieving efficient doping of OSCs for advanced organic electronic applications.

Sensitivity and Topology of Exceptional Rings in Nonlinear Non-Hermitian Planar Optical Microcavities - Wingenbach, Jan; Ares Santos, Laura; Ma, Xuekai; Sperling, Jan; Schumacher, Stefan (Arxiv)
Non-Hermitian systems hosting exceptional points (EPs) exhibit enhanced sensitivity and unconventional mode dynamics. Going beyond isolated EPs, here we report on the existence of exceptional rings (ERs) in planar optical resonators with specific form of circular dichroism and TE-TM splitting. Such exceptional rings possess intriguing topologies as discussed earlier for condensed matter systems, but they remain virtually unexplored in presence of nonlinearity, for which our photonic platform is ideal. We find that when Kerr-type nonlinearity (or saturable gain) is introduced, the linear ER splits into two concentric ERs, with the larger-radius ring being a ring of third-order EPs. Transitioning from linear to nonlinear regime, we present a rigorous analysis of spectral topology and report enhanced and adjustable perturbation response in the nonlinear regime. Whereas certain features are specific to our system, the results on non-Hermitian spectral topology and nonlinearity-enhanced perturbation response are generic and equally relevant to a broad class of other nonlinear non-Hermitian systems, providing a universal framework for engineering ERs and EPs in nonlinear non-Hermitian systems.

Quantifying Spin Defect Density in hBN via Raman and Photoluminescence Analysis - Patra, Atanu; Konrad, Paul; Sperlich, Andreas; Biktagirov, Timur; Schmidt, Wolf Gero; Spencer, Lesley; Aharonovich, Igor; Höfling, Sven; Dyakonov, Vladimir (Advanced Functional Materials)
Abstract Negatively charged boron vacancies () in hexagonal boron nitride (hBN) are emerging as promising solid‐state spin qubits due to their optical accessibility, structural simplicity, and compatibility with photonic platforms. However, quantifying the density of such defects in thin hBN flakes has remained elusive, limiting progress in device integration and reproducibility. Here, an all‐optical method is presented to quantify defect density in hBN by correlating Raman and photoluminescence (PL) signatures with irradiation fluence. Two defect‐induced Raman modes, D1 and D2, are identified and assigned them to vibrational modes of using polarization‐resolved Raman measurements and density functional theory (DFT) calculations. By adapting a numerical model originally developed for graphene, an empirical relationship linking Raman (D1, E 2g ) and PL intensities is established to absolute defect densities. This method is universally applicable across various irradiation types and uniquely suited for thin flakes, where conventional techniques fail. The approach enables accurate, direct, and non‐destructive quantification of spin defect densities down to 10 15 defects/cm 3 , offering a powerful tool for optimizing and benchmarking hBN for quantum optical applications.

Umkämpfte Semantiken des ‚Europäischen‘ in der Weltanschauungsliteratur der Zwischenkriegszeit - Heise, Tillmann (Forum Interdisziplinäre Begriffsgeschichte)

Forms of Understanding for XAI-Explanations - Buschmeier, Hendrik; Buhl, Heike M.; Kern, Friederike; Grimminger, Angela; Beierling, Helen; Fisher, Josephine Beryl; Groß, André; Horwath, Ilona; Klowait, Nils; Lazarov, Stefan Teodorov; Lenke, Michael; Lohmer, Vivien; et al. (Cognitive Systems Research)
Explainability has become an important topic in computer science and artificial intelligence, leading to a subfield called Explainable Artificial Intelligence (XAI). The goal of providing or seeking explanations is to achieve (better) ‘understanding’ on the part of the explainee. However, what it means to ‘understand’ is still not clearly defined, and the concept itself is rarely the subject of scientific investigation. This conceptual article aims to present a model of forms of understanding for XAI-explanations and beyond. From an interdisciplinary perspective bringing together computer science, linguistics, sociology, philosophy and psychology, a definition of understanding and its forms, assessment, and dynamics during the process of giving everyday explanations are explored. Two types of understanding are considered as possible outcomes of explanations, namely enabledness, ‘knowing how’ to do or decide something, and comprehension, ‘knowing that’ – both in different degrees (from shallow to deep). Explanations regularly start with shallow understanding in a specific domain and can lead to deep comprehension and enabledness of the explanandum, which we see as a prerequisite for human users to gain agency. In this process, the increase of comprehension and enabledness are highly interdependent. Against the background of this systematization, special challenges of understanding in XAI are discussed.
Keywords: understanding; explaining; explanations; explainable; AI; interdisciplinarity; comprehension; enabledness; agency

Operando Analysis of the Pre-OER Activation of Metal-Doped Co3O4 Nanoparticle Catalysts - Kampermann, L.; Klein, J.; Wagner, T.; Kotova, A.; Placke-Yan, C.; Yasar, A.; Jacobse, L.; Lasagna, S.; Leppin, Christian; Schulz, S.; Linnemann, Julia; Bergmann, A.; et al. (ACS Catalysis)
Doped Co3O4 nanoparticles are investigated via spectro-electrochemistry in the (pre-) oxygen evolution reaction (OER) regime by tracing the absorption signal of the Co3+ d–d transition under applied bias for getting insight into the catalysts activation and the formation of catalytically active phases. In the low potential regime up to 1.37 VRHE, a rise in the optical absorption signal of the [Co3+]oct d–d transition is observed and attributed to a structural change from [Co2+]tet to [Co3+]oct due to an electrochemically induced surface restructuring with water. For applied potentials higher than 1.37 VRHE an overall offset of the absorption spectra in the UV–vis range, equivalent to a darkening of the materials is detected. This is attributed to the formation of a CoOx(OH)y skin layer as supported by high-energy X-ray diffraction (HE-XRD) measurements. We found that the kinetics of the Co3+ states are heavily influenced by the type of dopant with V-doped Co3O4 exhibiting stable Co3+ states (>20 min) while the Mn-doped Co3O4 Co3+ states reduce within 36 s under reductive bias. We conclude that doping Co3O4 with transition metals affects the formation and potential-dependent thickness of the CoOx(OH)y skin layer as the catalytically active phase and the formation of long-time stable surface Co3+ states after activation in the first OER cycle.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; operando characterization; spectroelectrochemistry

What do metaphors of understanding hide? - Porwol, Philip Fabian; Scharlau, Ingrid (STUDIA NEOFILOLOGICZ: NEROZPRAWY JĘZYKOZNAWCZE (Modern Language Studies: Linguistic Essays))
Many previous studies on the conceptual function of metaphors have focused on their func-tion of highlighting aspects of target concepts. From the beginning of this research, it was knownthat conceptual metaphors also hide aspects of the target concept; however, this as-pect has been less studied. This study builds upon the idea that the hiding aspect of a specific metaphor should be identified in relation to other metaphors for the same concept. A method is presented to detail this relation based on the theory of semantic frames and the FrameNet resource to identify the hidden aspects and apply it to a corpus of 298 elicited metaphor texts on the target concept of understanding. The analysis revealed that certain conceptual aspects are consistently hidden by a majority of metaphors, pointing to patterns in conceptualization. Using this approach, six aspects frequently hidden by metaphors were identified: Sociality, Transfer, Ownership, Perception, Foundation and Duration.

Baked Apples and Bitter Ales: Richard Jefferies, Rural Health, and the Medical Imagination in Amaryllis at the Fair (1887) - Behler, Felix (8th Digital DACH Victorianists Workshop – Mediating Medicine: Health and Illness in the Victorian Age. Organisation: Dr. Julia Ditter (Universität Bremen), Dr. Anne Korfmacher (Universität Graz).)

Negotiating the future: legitimacy and power dynamics in Europe's twin transition - Lenz, Sarah (Sustainable Futures)

In Situ PM‐IRRAS and XPS Analysis of Nitrogen Plasma Surface Modification of Polylactide Thin Films - Golebiowska, Sandra Alicja; Voigt, Markus; de los Arcos, Teresa; Grundmeier, Guido (Surface and Interface Analysis)
ABSTRACT Spin‐coated polylactide (PLA) thin films were exposed to nitrogen plasma for varying time intervals. The progressive etching of the PLA film in direct contact with the nitrogen plasma was monitored in situ using polarization modulated infrared reflection absorption spectroscopy (PM‐IRRAS). No appreciative changes in composition were seen with PM‐IRRAS, indicating that the etching did not significantly affect the bulk composition. Atomic force microscopy characterization of the plasma‐etched films showed that the PLA films are homogeneously etched. Subsequent ex situ XPS analysis of the treated surface revealed the presence of C‐N bonds in the surface‐near region that could be associated with amino and/or amide surface species. PLA films were also alternatively exposed to nitrogen ion beams produced by an electron‐cyclotron‐resonance (ECR) plasma source and were investigated in vacuo by XPS. This treatment revealed the partial substitution of surface oxygen species by nitrogen, resulting in a similar surface modification as in the plasma case. The comparison of XPS data and water contact angle studies suggest that the activated surfaces show a reorientation of macromolecular fragments in the surface‐near region depending on the polarity of the phase with which they are in contact. Under ultra‐high vacuum (UHV) conditions, the surface tends to lower its surface energy, while in contact with the aqueous phase, subsurface polar groups orientate outwards, which enables the formation of hydrogen bonds.

A rate-based model for reactive separation columns with sandwich packings - Franke, Patrick; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y. (Chemical Engineering Science)
Sandwich packings are assembled from two conventional structured packings with different geometrical surface areas stacked alternatingly within a separation column. When operated under partially flooded conditions, they provide significant mass transfer improvement compared to common structured packings. In this work, a rate-based model including novel mass transfer correlations is presented and validated using a comprehensive experimental database for the reactive absorption of CO2 into aqueous monoethanolamine. The proposed rate-based approach is capable of accounting for axial dispersion, thereby enabling the evaluation of the effect of liquid-phase backmixing on the mass transfer performance. The validated rate-based model is used to evaluate the separation performance of sandwich packings. Compared with structured packings, up to 10 % higher mass transfer rates are obtained.
Keywords: Sandwich packings Structured packings Rate-based approach Model validation Ultra-fast X-ray tomography

A contribution to the mechanistic understanding of the improvement of the delamination resistance of adhesives on steel by grit-blasting - Ruhm, Lukas; Neßlinger, Vanessa; Becker, Roman; Meschut, Gerson; Grundmeier, Guido (International Journal of Adhesion and Adhesives)

Interface chemistry and adhesion of thin bilayer Si-organic PECVD barrier films on post-consumer recycled polypropylene - Müller, Hendrik; Cetin, Ali; Dahlmann, Rainer; de los Arcos, Teresa; Grundmeier, Guido (Surface and Coatings Technology)

Spontaneous grafting of nitrobenzenediazonium salt on plasma-modified copper substrates - Su, Jiangling; Muhle, Marius; Nembot, Nelly; Prüßner, Tim; Xie, Xiaofan; Wittstock, Gunther; Grundmeier, Guido (Electrochimica Acta)

Digitale Kompetenzen für Lehrkräfte in der beruflichen Bildung – Beiträge zur Modellierung, Messung und Förderung - Sänger, Niklas
Die digitale Transformation stellt Lehrkräfte vor eine doppelte Herausforderung: Sie sind selbst Lernende im Zuge des Wandels und gleichzeitig dafür verantwortlich, digitale Kompetenzen bei ihren Lernenden zu fördern. Aus Sicht der beruflichen Bildung besteht eine weitere Herausforderung darin, dass Lehrkräfte zwischen zwei inhaltlichen Referenzsystemen – wissenschaftsorientiertem Fachwissen und praxisbezogenem beruflichem Wissen – vermitteln müssen. Bisherige Forschungsarbeiten fokussieren jedoch primär medienpädagogische Aspekte und vernachlässigen den Einfluss der digitalen Transformation auf die fachlichen Lerngegenstände sowie damit verbundene fachdidaktische Implikationen. Die Dissertation adressiert diese Forschungslücke, indem sie untersucht, wie digitale Kompetenzen von Lehrkräften in der beruflichen Bildung konzeptualisiert, empirisch erfasst und curricular integriert werden können. Sie verfolgt dabei drei zentrale Fragestellungen: (1) Wie lassen sich digitale Kompetenzen im Kontext des doppelten Gegenstandsbezugs theoretisch fundieren? (2) Wie kann ein entsprechendes Kompetenzmodell empirisch operationalisiert werden? (3) Welche Implikationen ergeben sich daraus für die curriculare Gestaltung von Lehramtsstudiengängen? Im Rahmen der kumulativen Dissertation wird zunächst das TPACK-Modell kritisch analysiert und für den Kontext der beruflichen Bildung erweitert. Darauf aufbauend wird ein Messinstrument zur Erfassung digitaler Kompetenzen entwickelt und empirisch validiert. Zudem wird ein hochschuldidaktisches Konzept zur curricularen Integration digitaler Kompetenzen entwickelt und reflektiert. Die Ergebnisse zeigen, dass der doppelte Gegenstandsbezug ein zentrales Strukturmerkmal digitaler Kompetenzen in der beruflichen Bildung darstellt und bei der Ausbildung von Lehrkräften systematisch berücksichtigt werden muss. Die Dissertation leistet einen konzeptionellen und empirischen Beitrag für den Diskurs um digitale Kompetenzen in der beruflichen Bildung und gibt konkrete Impulse für die Professionalisierung von Lehrkräften im Zuge der digitalen Transformation.

Didaktische Überlegungen in der Psychologie - Scharlau, Ingrid; Jenert, Tobias (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)